ANALISIS PENGELOLAAN DANA DESA DALAM PEMBERDAYAAN MASYARAKAT DESA HANOFA KECAMATAN SIROMBU KABUPATEN NIAS BARAT TAHUN 2016-2020 - Maruhawa, Bela Kristin (Balance: Jurnal Riset Akuntansi dan Bisnis, 2022)
The scope of this research is a study on the management of village funds in Hanofa, Sirombu District, and West Nias Regency. This study aims to find out how the management of the Hanofa village funds, Sirombu District, West Nias Regency for the 2016-2020 fiscal year. The research method used in this research is qualitative research, with a descriptive approach. This research method is a method used to describe or analyze a research result. The results obtained in this study are the management of Hanofa village funds, Sirombu District, West Nias Regency including planning, implementation, administration, reporting and accountability. The management of village funds carried out by the Hanofa village government, Sirombu District, West Nias Regency has followed the technical guidelines that have been regulated in the legislation, so this study can conclude that the management of Hanofa village funds, Sirombu District, West Nias Regency for the 2016-2020 fiscal year is quite effective